ANÁLISIS COMPARATIVO DE LA PRESENTACIÓN PERSONAL VIRTUAL EN DIFERENTES ESPACIOS DE INTERACCIÓN - PhD Carlos ARCILA CALDERÓN (Fonseca, Journal of Communication, 2023)
This paper examines the presentation of a group of individuals in different virtual environments. The objective is to compare the communication of identity in each space and in different times, and to describe the effort held to each identity category, in order to know if the masks used by these individuals were the same (repeat) or changes (contradiction).